The Implications Of Social Responsibility In Reducing Youth Unemployment In Romania - Sorina-Geanina Stanescu; Comandaru (The Central European Review of Economics and Management (CEREM), 2019)
Aim: Lately, there is more and more discussion about sustainable development and social responsibility within organizations, thus increasing the pressure on organizations and managers to act ethically and responsibly. The main purpose of this study is to present how Romanian businesses have integrated aspects of social responsibility into the decision-making and management systems of organizations. The study focuses on identifying the main factors behind the development of the concept of social responsibility and presenting the link between economic activity and sustainable development. A major focus of this research is the study on the implications of corporate social responsibility in reducing the number of youth unemployment at national level.~Design/Research methods: As far as the methodology of research is concerned, we will start from the theoretical documentation and we will continue with empirical research, using descriptive analysis and statistical interpretation of data as the main research methods.~Conclusions/findings: Empirical research conducted in this paper allowed us to observe the involvement of organizations in adopting support measures for the social problems of young people unemployed.~Originality/value of the article: Social responsibility is a vast concept that is growing in Romania and the implication of this concept in solving unemployment has led us to realize the present research that we want to add value to both the business environment in Romania and young researchers interested in this field.
Keywords: Q56; 330; management; social responasability; youth unemployment